A different cardiac resynchronization therapy technique might be needed in some patients with nonspecific intraventricular conduction disturbance pattern-final results. (25th November 2020) - Vereckei, A; Katona, G; Szelenyi, Z; Kozman, B; Szenasi, G
Abstract: Background: Current cardiac resynchronization therapy (CRT) works by pacing the latest activated left ventricular (LV) site. We hypothesized that the greater nonresponse rate of patients with nonspecific intraventricular conduction disturbance (NICD) than with left bundle branch block (LBBB) pattern to CRT might be due, besides less dyssynchrony, to the inability of the current CRT technique, devised to eliminate dyssynchrony caused by LBBB pattern, to eliminate dyssynchrony in some patients with NICD pattern, because their latest activated LV site is far away from that in LBBB. Methods: We devised a novel surface ECG method to estimate the approximate location of the latest activated LV site based on the principle that the resultant ST vector of secondary ST segment alterations associated with wide QRS complexes is directed 180o away from the latest activated LV site. By measuring the amplitude and polarity of secondary ST segment alterations in two optional frontal and horizontal plane ECG leads and using a software, we determined the resultant 3D spatial secondary ST vector in 88 patients with LBBB and 57 patients with NICD patterns and heart failure. To validate the ECG method, we also estimated the latest activated LV region by echocardiography using 3D parametric imaging and 2D speckle tracking in 16 LBBB and 13 NICD patients. Patients with NICD pattern were subdivided according to their non-overlapping frontal plane resultant secondary ST vector ranges to NICD-1 (n=35) and NICD-2 (n=22) subgroups. Results: The resultant 3D spatial secondary ST vector coordinates in the LBBB group were: (x axis: −0.228 mV, y axis: −0.062 mV, z axis: 0.63 mV); in the NICD-1 and NICD-2 subgroups: (x: 0.154 and 0.198 mV, y: −0.198 and 0.162 mV, z: 0.422 and 0.398 mV respectively). Consequently the latest activated LV sites were located leftward, posterosuperior in the LBBB group, right, posterosuperior in the NICD-1 and right, posteroinferior in the NICD-2 subgroups. The latest activated LV region determined by ECG and echocardiography matched in all patients, except 1. Conclusions: The latest activated LV site was at the expected position in the LBBB group, while it was at an almost opposite site in the NICD-2 group [22/57 (39%)]. Thus, one potential reason for the unfavorable response to CRT, occurring in approx. 40% of patients with NICD pattern with a QRS duration of 120–149 ms in randomized studies, is that the current CRT technique using a left posterolateral LV electrode position may not be able to eliminate dyssynchrony in these patients. Funding Acknowledgement: Type of funding source: None